Habit drives sustainable tourist behaviour. (January 2022) - MacInnes, Sarah; Grün, Bettina; Dolnicar, Sara
Abstract: Most practical interventions the tourism industry deploys to make tourists behave in more environmentally sustainable ways when they are at their premises or destination – such as the request to reuse towels to protect the environment – rely on attention and cognitive processing. We propose that focusing instead on habit, as the key construct, will be more effective in achieving behavioural change. This study discusses the – largely neglected – role of habit in our understanding of tourist behaviour and provides initial empirical proof of concept of the explanatory power of habit. Findings suggest that entirely new types of behavioural interventions should be developed, which aim at breaking bad vacation habits through disrupting automaticity, such as reducing plate size to prevent overfilling of plates at the buffets, and re-establishing good habits people enact at home, such as by asking people to treat the hotel the same way they do their own home. Graphical abstract: Unlabelled Image Highlights: Dominant social science theories fail to explain pro-environmental tourist behaviour. We propose habit as a key driver of tourists' pro-environmental behaviours. An empirical study provides proof of concept. The new theory is a promising basis for developing behaviour change interventions.